PENGARUH PENGAWASAN KERJA DAN DISIPLIN KERJA TERHADAP PRODUKTIVITAS KARYAWAN (Kasus Bagian Pengolahan PT. Mitra Aung Swadaya (MAS) Kecamatan Kelayang Kabupaten Indragiri Hulu) - Rofli Sulistiyo Baktiyasa; Lena Farida (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This study was to determine the Influence of Work Supervision And Work Discipline on Employee Productivity (Case Processing Part PT. Mitra Agung Swadaya (MAS) District of Kelayang Indragiri Hulu). This research is located in South Cross Street, Sungai Golang Village, District Of Kelayang Indragiri Hulu. The population of this study were all employees in PT. Mitra Agung Swadaya (MAS) part processing numbering 49 people. Data analysis in this study using SPSS. Sampling technique is a method uses census and testing techniques used in this study include validity test, reliabilitas test, multiple linier, regression analysis, t-test and f-test to test and prove the research hypothesis.Result of analysis with spss program, the result of relationship between supervision of work (X1) and discipline work (X2) with employee productivity (Y) has a very strong relationship. Partially, supervision of work (X1) have a significant effect on employee productivity, while the work discipline variable(X2) have a significant effect on employee productivity.Keywords : Work Supervision, Work Discipline, Employee Productivity